2016
DOI: 10.1007/s10934-016-0227-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing conditions on the properties of recycled cathode ray tube glass foams

Abstract: Cathode ray tube glass waste was used to produce glass foams by a powder sintering route. The glass waste powder was mixed with small amounts (5 and 8 wt%) of coal fly ash, which acted as foaming agent, and the compacts of the mixed powders were heated at different sintering temperatures in the range 600-800°C for various dwell times (30-120 min). The effect of the different processing conditions on the microstructural characteristics (porosity, pore size and pore size distribution), mechanical resistance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Based on this fact, it can be suggested that temperatures superior to 750°C will have a more significant influence on the structure of glass foams, which is in agreement with other studies. 27,32,36 Normal plots of residuals are shown in Figure 5 to check the model used to estimate the effects. In this case, a model is said to be valid when the residuals plotted lie close to the line.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this fact, it can be suggested that temperatures superior to 750°C will have a more significant influence on the structure of glass foams, which is in agreement with other studies. 27,32,36 Normal plots of residuals are shown in Figure 5 to check the model used to estimate the effects. In this case, a model is said to be valid when the residuals plotted lie close to the line.…”
Section: Resultsmentioning
confidence: 99%
“…Several foaming agents to manufacture of glass foams are reported: sodium hydroxide, 25 porcine bones, 26 coal fly ash, 27 sodium carbonate, 19,20 carbon black, 28 silicon carbide, 29 calcium carbonate, and even eggshells. 2,30,31 In addition to foaming agents, other additives can be added to foams to modify their properties or facilitate processing.…”
Section: Introductionmentioning
confidence: 99%
“…Millions of tons of SLS glass are produced (and become waste) worldwide in the form of container and float glass products [23]. Commercial foam glasses have 45-85 vol% porosity, 0.1-1.2 g/cm 3 apparent density, 0.4-6 MPa compressive strength, and 0.1-0.2 W/mK thermal conductivity [24][25][26][27][28][29]. Compressive strength is particularly important in the case of foam glass used in complex embankment applications as filling material to reduce vertical and lateral soil pressures, and to increase slope stability.…”
Section: Introductionmentioning
confidence: 99%
“…From an economical and environmental point of view, researchers use several waste materials, such as fly ash [30], cathode ray tube (CRT) glass, red mud, mineral wool waste [31,32], flat panel, and tailing waste [33] to produce building material [2,16,21,24,[34][35][36][37][38][39][40]. The amount of CRT glass arising from computer monitors and TV sets increases dramatically due to their replacement by the liquid crystal display (LCD) [41,42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation